R and D best practices, absorptive capacity and project success (2015)
Research and Development (R and D) project management style in companies can be different according with their size and technological intensity. R and D Projects are characterized by high technical and economic uncertainty. And their execution carried out a learning process, although its aims were achieve the results planned. Results from a sample of 71 Spanish firms evidence that best practice in R and D project management promote the innovation in two ways. The purpose of practices is positively related to absorptive capacity of knowledge (CAC) in the organisation, and in turn, CAC affects the success of R and D projects.